A Bioactive Extract Rich in Triterpenic Acid and Polyphenols from Olea europaea Promotes Systemic Immunity and Protects Atlantic Salmon Smolts Against Furunculosis - Salomón, Ricardo; Furones, M. Dolors; Reyes-López, Felipe E.; Tort, Lluis; Firmino, Joana P.; Esteban, M. Angeles; Espinosa Ruíz, Cristóbal; Quintela, José C.; Pinilla-Rosas, José M.; Vallejos-Vidal, Eva; Gisbert, Enric (Frontiers in Immunology, 2021)
In the present study, the modulation of the transcriptional immune response (microarray analysis) in the head kidney (HK) of the anadromous fish Atlantic salmon (Salmo salar) fed a dietary supplementation of olive fruit extract (AQUOLIVE®) was evaluated. At the end of the trial (133 days), in order to investigate the immunomodulatory properties of the phytogenic tested against a bacterial infection, an in vivo challenge with Aeromonas salmonicida was performed. A total number of 1027 differentially expressed genes (DEGs) (805 up- and 222 down-regulated) were found when comparing the transcriptomic profiling of the HK from fish fed the control and AQUOLIVE® diets. The HK transcripteractome revealed an expression profile that mainly favored biological processes related to immunity. Particularly, the signaling of i-kappa B kinase/NF-kappa and the activation of leukocytes, such as granulocytes and neutrophils degranulation, was suggested to be the primary actors of the innate immune response promoted by the tested functional feed additive in the HK. Moreover, the bacterial challenge lasted 12 days at the end of the assay, showed that the cumulative survival was higher in fish fed the AQUOLIVE® diet (96.9 ± 6.4%) than in fish from the control group (60.7 ± 13.5%). These results indicate that the dietary supplementation of the functional feed additive AQUOLIVE® at level of 0.15% enhanced the systemic immune response in Atlantic salmon smolts as the combined analysis of the HK transcriptomic profiling and results from the A. salmonicida challenge indicated.